2020
DOI: 10.1186/s12935-020-01675-0
|View full text |Cite|
|
Sign up to set email alerts
|

SLC39A1 contribute to malignant progression and have clinical prognostic impact in gliomas

Abstract: Background Gliomas are one of the most common primary tumors of the central nervous system, and have an unfavorable prognosis. SLC39A1 is a zinc ion transport protein which inhibits the progression of prostate cancer. By studying the role and mechanism of SLC39A1 in the progression of gliomas, perhaps a new therapeutic target can be provided for their treatment. Method The TCGA, CCGA, GSE16011, GSE44971 and GSE11260 data sets were employed to evaluate the expression level of SLC39A1 in paracancerous and gliom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…As for the detailed tumor-related functions, our in vitro and in vivo data proved that SLC39A1 overexpression can promote gastric adenocarcinoma proliferation, while SLC39A1 knockdown suppressed tumor growth. Consistent with our findings, Wang et al demonstrated that SLC39A1 promoted proliferation of glioma cells and inhibited their apoptosis [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As for the detailed tumor-related functions, our in vitro and in vivo data proved that SLC39A1 overexpression can promote gastric adenocarcinoma proliferation, while SLC39A1 knockdown suppressed tumor growth. Consistent with our findings, Wang et al demonstrated that SLC39A1 promoted proliferation of glioma cells and inhibited their apoptosis [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, in silico analyses did not find its correlation with breast cancer prognosis [ 17 , 18 ]. Recently, Wang's study revealed that SLC39A1 was highly expressed in gliomas and negatively correlated with glioma outcome [ 14 ], highlighting its involvement in different malignancies. As for the detailed tumor-related functions, our in vitro and in vivo data proved that SLC39A1 overexpression can promote gastric adenocarcinoma proliferation, while SLC39A1 knockdown suppressed tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While an increase in SLC39A1 mRNA levels were not observed in all individuals from the treated group [349], comparable results have been obtained in humans by another group, demonstrating an increased ZIP1 mRNA expression in lymphocytes in an Australian elderly population supplemented with Zn [350]. Lastly, ZIP1 is associated with various cancers [351][352][353], including pancreatic [287] and prostate [354][355][356][357] cancer.…”
Section: Zip1 (Slc39a1)supporting
confidence: 81%
“…Wang et al demonstrated that SLC39A1 overexpression promotes tumor progression and correlates with unfavorable clinical outcomes in glioma. 14 In addition, downregulation of SLC39A1 impairs the accumulation of zinc in tumor cells, thereby promoting the malignant phenotype of prostate cancer. 15 , 16 However, little is known about the regulatory mechanism of SLC39A1 in HCC progress.…”
Section: Introductionmentioning
confidence: 99%